Contribution of non‐reference alleles in mtDNA of Alzheimer's disease patients. (11th March 2014) - Casoli, Tiziana; Di Stefano, Giuseppina; Spazzafumo, Liana; Balietti, Marta; Giorgetti, Belinda; Giuli, Cinzia; Postacchini, Demetrio; Fattoretti, Patrizia; Conti, Fiorenzo
Abstract Many observations suggest that mutations of mitochondrial DNA (mtDNA) could be responsible for the neurodegenerative changes of Alzheimer's disease (AD). Here we examined the signal intensity of the four alleles of each mtDNA nucleotide position (np) in whole blood of AD patients and age‐matched controls using MitoChip v2.0 array. Our analysis identified 270 significantly different nps which, with one exception, showed an increased contribution of non‐reference alleles in AD patients. Principal component analysis (PCA) and cluster analysis showed that five of these nps could discriminate AD from control subjects with 80% of cases correctly classified. Our data support the hypothesis of mtDNA alterations as an important factor in the etiology of AD.